Optimization of immunofluorescence protocols for detection of biomarkers in colorectal and breast cancer tissues - Gurvits, Natalia (fi=Turun yliopisto|en=University of Turku|, 2016)
Cancer remains an undetermined question for modern medicine. Every year millions of people ranging from children to adult die since the modern treatment is unable to meet the challenge. Research must continue in the area of new biomarkers for tumors. Molecular biology has evolved during last years; however, this knowledge has not been applied into the medicine. Biological findings should be used to improve diagnostics and treatment modalities. In this thesis, human formalin-fixed paraffin embedded colorectal and breast cancer samples were used to optimize the double immunofluorescence staining protocol. Also, immunohistochemistry was performed in order to visualize expression patterns of each biomarker. Concerning double immunofluorescence, feasibility of primary antibodies raised in different and same host species was also tested. Finally, established methods for simultaneous multicolor immunofluorescence imaging of formalin-fixed paraffin embedded specimens were applied for the detection of pairs of potential biomarkers of colorectal cancer (EGFR, pmTOR, pAKT, Vimentin, Cytokeratin Pan, Ezrin, E-cadherin) and breast cancer (Securin, PTTG1IP, Cleaved caspase 3, ki67).